Synergistic interaction of lime, boron and molybdenum on curd rot and curd yield of cauliflower (Brassica oleacea conver botrytis var botrytis) on an Alfisol - KOTUR, SHIVAPUTRA C (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1989-92 on 'Pusa Snowball 1 ' cauliflower [Brassica oleracea L. convarbatrytis (L.) Alef. var batrytis L.] to find out the interaction of lime (0 and 3.4 tonnes/ha applied to soil), boron (1.5 kgB/ha applied to soil and 3 foliar. sprays of 0.1 % boric acid) and molybdenum (1.5 kg Mo/ha applied to soil and 3 foliarsprays of 0.1 % ammonium molybdate). Lime application significantly increased the curd Yield, Mo and Ca contents ofleaf tissue, net returns/ha and depressed boron content of leaf tissue. Soil/foliar application of boron and molybdenumapplication signilcantly increased curd yield and the respective nutrient contents in leaf tissue compared with thecontrol. Boron application significantly reduced curd-rot caused by boron deticiency and resulted in high net returns.Combined application of boron and molybdenum to soil synergistically increased the curd yield by 12 and 17% comparedwith boron and molybdenum applied alone while the increase was significantly higher (17 and 27%) whenapplied through foliar sprays. Lime application to soil combined with 3 foliar sprays of 0.1 % boric acid and 0.1 %ammonium molybdate together are optimum for high curd yield, low curd rot and high net returns for cauliflowergrown on Alfisols of Bihar plateau.